ANALISIS PENDAPATAN PRODUKSI SAGU (Metroxylon Sagu) DI NEGERI RUTONG KECAMATAN LEITIMUR SELATAN KOTA AMBON - Esterlina Matayane; Agustinus Kastanya; Troice Siahaya (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
The aim of the research is to understand the contribution of farmers to production and the factors that influence sago (Metroxylon sago) production in Negeri Rutong, South Leitimur District, Ambon City. The research method used is the survey method. The results of the research show that the income of Sago (Metroxylon sago) production farmers in Rutong State contributes IDR 235,625,000 (57.85%) with an average per month per Head of Family of IDR. 785,417. Farmers' income outside of sago production (Metroxylon sago) or side income is IDR 171,671,000 (42.15%) and the average per month per head of family is IDR. 572,237. Sago production income (Metroxylon sago) in Rutong country has a very large contribution value when compared to the value of income outside sago production (Metroxylon sago). If converted into monthly time units, the income is IDR IDR. 785,417 lower than Ambon City's UMK of Rp. 2,991,299.